Manipulative Potential of Colour Names in Creolized Texts of Decorative Cosmetics Advertising (by Material of French and Russian Languages) - L. R. Abdullina; E. V. Artamonova (Научный диалог, 2019)
The article is devoted to the pragmatic component of a choice of colour names in the advertising Internet discourse. Attention is paid to the concept of creolized text in advertising. The importance of colour in this type of texts is substantiated. The object of the research is colour naming for decorative cosmetics in French and Russian languages. The material of the study is the data obtained from the sites of the leading Russian- and French-language online stores of cosmetics. In the course of comparative analysis the problem of informative capacity of colour names is considered, and their influence on the psycho-emotional sphere of the potential consumer is established. How to manipulate the mind of a recipient by method of the metaphorization of colour names is demonstrated, in which certain layer is of synesthetic metaphors. In the study of the psychological component the authors describe the appeal of copywriters to the emotions, the psychological state of the individual. There are gender-oriented and spiritual-cultural conditionality of colour names of products of decorative cosmetics. It is proved that colour designations appeal to spiritual values, national stereotypes, cultural and historical memory of an addressee. It is concluded that the use of borrowings registered in both languages, the actualization of different meanings of the lexical-semantic field of one word, the appeal to the semes of language units for the formation of the associative-colour image among consumers testify to the language game used by copywriters for the implementation of manipulative influence on an addressee.